Participatory Mangrove Ecosystem Rehabilitation by PT Pertamina Patra Niaga Fuel Terminal Pulau Baai on the Coast of Bengkulu City - Fitrianto, Yusman; Heydinal, Havialdo; Darmawan, Arief; Sumarjo, Tri Ahmad; Idham, Jonni (Universitas Dehasen Bengkulu, 2025)
The destruction of mangrove ecosystems in various coastal areas of Indonesia has threatened the environmental balance and the livelihoods of communities that depend on coastal resources. In the coastal area of Baai Island, Bengkulu City, pressure on mangrove ecosystems has increased due to industrial activities, land conversion, and low public awareness of the importance of environmental conservation. In response to this situation, PT Pertamina Patra Niaga Fuel Terminal Pulau Baai initiated a community-based mangrove rehabilitation program as part of its corporate social responsibility (CSR/TJSL). The program was implemented over a period of four months and involved various parties, including civil society organizations (Yakesma Bengkulu), local communities, and the Bengkulu City Government. Core activities of the program included planting and maintaining 2,025 Rhizophora mucronata mangrove seedlings, technical training, and participatory growth monitoring. This collaborative approach aims not only to restore the ecological functions of the coastal area but also to foster community awareness and ownership of the environment. The results of the implementation demonstrate that active community involvement enhances the effectiveness of rehabilitation activities, strengthens local capacity, and opens opportunities for replicating the program in other coastal areas. This program shows that community-based mangrove rehabilitation initiatives launched by companies through CSR schemes can serve as a sustainable strategy for environmental conservation and community empowerment.